Long-Run Effects of Public Sector Sponsored Training in West Germany - Ruth Miquel; Michael Lechner; Conny Wunsch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Between 1991 and 1997 West Germany spent on average about 3.6 bn Euro per year on public sector sponsored training programmes for the unemployed. We base our empirical analysis on a new administrative data base that plausibly allows for selectivity correction by microeconometric matching methods. We identify the effects of different types of training programmes over a horizon of more than seven years. Using bias corrected weighted multiple neighbours matching we find that all programmes have negative effects in the short run and positive effects over a horizon of about four years. However, for substantive training programmes with duration of about two years gains in employment probabilities of more than 10% points appear to be sustainable, but come at the price of large negative lock-in effects.
Keywords: J68; 330; Active labour market policy; matching estimation; programme evaluation; panel data; Arbeitsvermittlung; Berufsbildung; Projektbewertung; Deutschland